Volunteers in the Late Byzantine Army: to the Question of Thelematarioi - Vladimir A. Zolotovskiy (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2017)
This paper focuses on the problem of a volunteer’s service at the late Byzantium military organization. The goal of the present research work is to determine the functional significance of the thelematarioi term. According to the analysis of narrative sources and act materials, the author concludes that the current state of the sources does not allow us to single out the thelematarioi as a special group of the byzantine population that had a special legal status associated with the military service. The term thelematarioi as an independent lexeme with a special functional military-technical and socio-legal content entered the science solely because of its mention of George Pachymeres in the context of describing events of particular importance to the empire. The author concludes that the thelematarioi was only one of the terms for volunteers involved in military service. Besides, as part of the problem statement, the author makes a preliminary conclusion that the volunteer service was of an organized nature supported by an independent special management system. The composition of volunteer military units that participated in the most important events of the Early Paleologian period was represented by migrant soldiers from among the Romanian’s peasants who knew warfare perhaps as stratiotes and deprived of their own lands, weapons, horses, etc. As they were forced to look for sources of income, if necessary, this part of the Byzantine population was able to attract to military service for fee, reinforcing the basic composition of the troops. Obviously, the weakness of weapons in combination with the professional skills of the soldiers predetermined their placement in the rearguard in the Battle at Apros.